Governance and management of urban trees and green spaces in South Africa: ensuring benefits to local people and the environment - Chishaleshale, Mwale (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
In the face of rapid urbanization and global climate change, urban trees and green spaces (UTGS) can contribute to the welfare of people and the urban environment. Urban trees and green spaces can assist to address urbanization challenges related to environmental degradation. While functions of UTGS have been well documented in the developed world, they have not yet received full attention in much of sub-Saharan Africa. Consequently, UTGS are under threat from urban development and fragmentation. Notably, the problems associated with UTGS also fall into the governance realm and indications are that poor governance and management of UTGS can negatively influence the potential benefits of UTGS to local people and the environment. This formed a basis for this research. The main objective of the study was to determine the current governance and management approaches to UTGS in South Africa. Through document search and review, the study determined the governance institutions influencing UTGS at national level and at provincial level (in the Limpopo and Eastern Cape Provinces). Face-to-face and online survey methods were used to determine the extent to which 28 local municipalities had adopted planned, systematic and integrated management of UTGS. The snowball approach was used to determine the key actors involved in UTGS activities and interviews were conducted to establish the roles and capabilities of these actors. A total of 540 household interviews were conducted to determine the institutional factors influencing local peoples' ability to access, plant and use UTGS. The findings of the study showed that UTGS have not been adequately covered in existing governance institutions and practice at national and provincial levels. Local government municipalities were not managing their UTGS in a planned or systematic manner due to constraining factors such as insufficient funds, insufficient personnel, lack of equipment and lack of political support. Only 7.1 % of the surveyed municipalities had an urban tree management plan and an estimate of the urban tree stock; 32.1 % had tree policies; 28.6 % had tree bylaws; 21.4 % had tree planting schedules; 10.7 % had tree maintenance schedules and only 3.6 % had tree inspection schedules. Key actors involved in UTGS activities differed among levels of government. The actors included national and provincial government departments, local government municipalities, Non-Governmental Organizations, private sector companies and local volunteers. Most of the actors, however, either planted trees or provided tree seedlings to municipalities and the local people. Tenure security was a key institutional factor affecting peoples' ability to plant, use or even remove trees from their residential plots. The same applied to trees in the streets and public parks. Whereas most respondents did not require permission to plant (79.8 %) or remove (75 %) trees on their residential plots, a majority of them required permission to plant and remove trees from streets (over 70 %) and public parks (over 80 %). However, with regard to planting and removing urban trees in public open spaces, 54% of the respondents indicated that permission was not required suggesting a lack of clarity among local residents on the issue. Overall, the findings of this study indicate that there is no political recognition and support for UTGS at almost all levels of government. This has resulted in the lack of incorporation of UTGS in urban planning and development and has caused UTGS to receive limited funding to permit planned and systematic management. Given the current rates of urbanization and urban development, the lowly prioritised UTGS are vulnerable to exploitation. To conserve UTGS and promote their potential contribution to local people and the environment, UTGS must be recognized and placed on political and development agendas. There is a need to develop national guidelines for UTGS management, assess the extent of the urban forest resource in local municipalities, clearly define the roles and capabilities of different actors, integrate UTGS in the urban planning and development system, and most of all seek to involve the local people in overall management and governance of UTGS.
Keywords: Trees in cities -- South Africa; Urban forestry -- South Africa; Community forestry -- South Africa; City planning -- South Africa; Human-plant relationships -- South Africa; Urban ecology (Biology -- South Africa; Urban ecology (Sociology) -- South Africa; Natural resources -- South Africa; Trees in cities -- Law and legislation -- South Africa